The advantage of scoring just before the half-time break - pure myth? Quasi-experimental evidence from European football - Meier, P.; Flepp, R.; Ruedisser, M.; Franck, E. (Journal of Sports Economics, 2020)
We examine whether the moment just before the half-time break is a particularly good time to score a goal. Using detailed data from the top five European football leagues between the 2013-2014 and 2017-2018 seasons, we exploit the quasi-random occurrence of goals scored just before and just after the half-time break. In the former situation, the game is exogenously interrupted by a break immediately after the goal, whereas in the latter situation, the game continues without interruption. We show that in the case of a goal being scored just before halftime, the scoring team benefits more from the half-time break than the conceding team.